Psychological Stress in the Mothers of Children with Autism Spectrum Disorder in Terms of Some Variables - Dagamseh, Bayan Izzeddine AL (International Journal of Membrane Science and Technology, 2023)
This study aimed to detect the level of psychological stress in the mothers of children with autism spectrum disorder in terms of some variables, and to attain that, the researcher built a scale to measure psychological stress in mothers by referring to the theoretical literature. The study scale included (6) Dimensions included in (53) paragraphs. The validity of the tool was confirmed by presenting it to a number of arbitrators with experience in the field of psychological counseling, and making sure that it was stable using the stability coefficient Alpha Cronbach, which amounted to (0.98) for the scale in total, the researcher used the descriptive method to verify to answer the questions of the study, the researcher calculated the mean and standard deviations of the responses of the mothers of the subjects. The general mean of the total score of the psychological stress scale was average with a mean of (3.02), in addition to the presence of significant differences at the level of significance (0.05 = ?) in the degree of psychological stress in mothers with autism spectrum disorder due to the variable of the educational level of the mother, marital status and the severity of disability, where the (8.213), the maternal stress scale showed the absence of a statistically significant above depending on the variable of disability severity and its value was (8.532). In light of the results of the study, the researcher made a number of recommendations to alleviate psychological stress in the mothers of children with autism spectrum disorder, and work on developing strategies to solve the problem of psychological stress in the mothers of people with autism spectrum disorder by referring to previous studies and taking experiences from them, in addition to holding training courses for mothers on how to deal with their children with autism spectrum disorder.